How people-centred health systems can reach the grassroots: experiences implementing community-level quality improvement in rural Tanzania and Uganda. Issue 1 (22nd September 2014) - Tancred, Tara; Mandu, Rogers; Hanson, Claudia; Okuga, Monica; Manzi, Fatuma; Peterson, Stefan; Schellenberg, Joanna; Waiswa, Peter; Marchant, Tanya; ,
Abstract: Background Quality improvement (QI) methods engage stakeholders in identifying problems, creating strategies called change ideas to address those problems, testing those change ideas and scaling them up where successful. These methods have rarely been used at the community level in low-income country settings. Here we share experiences from rural Tanzania and Uganda, where QI was applied as part of the Expanded Quality Management Using Information Power (EQUIP) intervention with the aim of improving maternal and newborn health. Village volunteers were taught how to generate change ideas to improve health-seeking behaviours and home-based maternal and newborn care practices. Interaction was encouraged between communities and health staff. Aim To describe experiences implementing EQUIP's QI approach at the community level. Methods A mixed methods process evaluation of community-level QI was conducted in Tanzania and a feasibility study in Uganda. We outlined how village volunteers were trained in and applied QI techniques and examined the interaction between village volunteers and health facilities, and in Tanzania, the interaction with the wider community also. Results Village volunteers had the capacity to learn and apply QI techniques to address local maternal and neonatal health problems. Data collection and presentation was a persistent challenge for village volunteers, overcome through intensive continuous mentoring and coaching. Village volunteers complemented health facility staff, particularly to reinforce behaviour change on health facility delivery and birth preparedness. There was some evidence of changing social norms around maternal and newborn health, which EQUIP helped to reinforce. Conclusions Community-level QI is a participatory research approach that engaged volunteers in Tanzania and Uganda, putting them in a central position within local health systems to increase health-seeking behaviours and improve preventative maternal and newborn health practices.